Does Accident Remind Us of Negligence - or Does Negligence Remind Us of Accident? - Case Report - Aslan, Fatmagül; Yaşar Teke, Hacer; Kıhtır, Hasan Serdar; Pakiş, Işıl (The Bulletin of Legal Medicine, 2023)
In this study, a child case who was admitted to the hospital with a history of falling from a height, and forensic medical consultation was requested due to a conflict between severe clinical findings and history, will be presented and attention will be drawn to the fact that abuse and neglect can underlie every accident, especially in children. A 3-year-old girl was referred to the hospital by her refugee family with a history of falling from a height of 4 meters onto a concrete floor at noon. Childhood physical traumas are situations that need to be investigated thoroughly, may be caused by neglect and abuse, and a multidisciplinary approach should be exhibited. In this regard, child health professionals; they can play important roles in many stages, from prevention, reporting and treatment to child protection and monitoring services.